Discounting the Future: on Climate Change, Ambiguity Aversion and Epstein-Zin Preferences - Stan Olijslagers; Sweder van Wijnbergen (Tinbergen Institute, 2019)
We focus on the effect of preference specifications on the current day valuation of future outcomes. Specifically, we analyze the effect of risk aversion, ambiguity aversion and the elasticity of intertemporal substitution on the willingness to pay to avoid climate change risk. The first part of the paper analyzes a general disaster (jump) risk model with a constant arrival rate of disasters. This provides useful intuition in how preferences influence valuation of long-term risk. The second part of the paper extends this model with a climate model and a temperature dependent arrival rate. Since the model yields closed form solutions up to solving an integral, our model does not suffer from the curse of dimensionality of numerical IAMs with several state variables. Introducing Epstein-Zin preferences with an elasticity of substitution higher than one and ambiguity aversion leads to much larger estimates of the social cost of carbon than obtained under power utility. The dominant parameters are the risk aversion coefficient and the elasticity of intertemporal substitution. Ambiguity aversion is of second order importance.
Keywords: Q51; Q54; G12; G13; 330; Social Cost of Carbon; Ambiguity Aversion; Epstein-Zin preferences; Stochastic Differential Utility; Climate Change